Guinea-Bissau : Enhanced Initiative for Heavily Indebted Poor Countries-Completion Point Document and Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
According to IMF and IDA authorities, Guinea-Bissau had met the requirements for reaching the decision point under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative. The authorities appreciated the country's tremendous efforts to reestablish economic, social, and institutional stability. In view of this, in addition to debt relief agreed at the decision point under the Enhanced Initiative for HIPC, they also agreed to topping up assistance at the completion point.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet